2019
DOI: 10.1186/s12964-019-0412-9
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen inhibits autophagy and promotes growth of endometrial cancer by promoting glutamine metabolism

Abstract: Background Excessive estrogen exposure is an important pathogenic factor in uterine endometrial cancer (UEC). Recent studies have reported the metabolic properties can influence the progression of UEC. However, the underlying mechanisms have not been fully elucidated. Methods Glutaminase (GLS), MYC and autophagy levels were detected. The biological functions of estrogen-MYC-GLS in UEC cells (UECC) were investigated both in vivo and in vitro. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 42 publications
(40 reference statements)
2
38
0
1
Order By: Relevance
“…Nevertheless, some insights can still be obtained from studies on autophagy in uterine corpus endometrial carcinoma (UCEC) cells. Consistent with estrogen's inhibitory effect on the autophagy of ESCs, our previous studies also show that estrogen significantly restricts autophagy of UCEC cells in vitro and in vivo 26 , 27 . Many drugs targeting autophagy-suppression are already in clinical use for endometrial hyperplasia 28 .…”
Section: Autophagy-related Molecules During the Menstruation Cyclesupporting
confidence: 74%
See 1 more Smart Citation
“…Nevertheless, some insights can still be obtained from studies on autophagy in uterine corpus endometrial carcinoma (UCEC) cells. Consistent with estrogen's inhibitory effect on the autophagy of ESCs, our previous studies also show that estrogen significantly restricts autophagy of UCEC cells in vitro and in vivo 26 , 27 . Many drugs targeting autophagy-suppression are already in clinical use for endometrial hyperplasia 28 .…”
Section: Autophagy-related Molecules During the Menstruation Cyclesupporting
confidence: 74%
“…However, PPD downregulates the expression of ERα, upregulates the expression of progesterone receptors (PGRs), which restricts estrogen-mediated anti-autophagy effects in ESCs 38 . Moreover, fulvestrant is a selective ER antagonist that can abrogate the inhibitory effect of estrogen on autophagy in UCEC cells 26 .…”
Section: Autophagy-related Molecules During the Menstruation Cyclementioning
confidence: 99%
“…In the field of endometrial cancer research, it has been reported that isoliquiritigenin (ISL) can induce autophagy in endometrial cancer cells, thereby exerting a cancer-suppressing effect [ 29 ]. High levels of estrogen affect glutathione metabolism by increasing the level of glutaminase, thereby inhibiting autophagy in endometrial cancer and promoting its growth [ 30 ]. Kanda R, et al showed that glucagon-like peptide-1 receptor (GLP-1R) promotes autophagy in endometrial cancer, thereby inhibiting its growth and suggesting GLP-1R agonists as a potential therapeutic strategy [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…p62/Sqstm1 gene is a well-known autophagy marker (Gómez-Sánchez et al, 2016). Recent study showed that estrogen inhibits autophagy in endometrial cancer (Zhou et al, 2019). Neuroprotective effects of E2 in peripheral neurons are partly related to the suppression of excessive autophagy (Lin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%